CLINICAL MANAGEMENT OF PEMPHIGUS USING AZATHIOPRINE IN A LABRADOR RETRIEVER - Navjot Singh Thakur; M.A. Ensha Lomiya; R. Raguvaran; Siddharth Chaudhary; `, K. Kavitha; Amit Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2026)
An array of autoimmune diseases that cause blisters and damage to the skin and mucous membranes is known as the pemphigus complex. It is marked by the development of autoantibodies directed towards keratinocyte adhesion molecules. Clinical signs include crusts, erosions, erythema, macules, pustules and hyperkeratosis. These lesions are typically found on the foot pad, nasal planum, ear margins and ear pinna etc. There can also be generalized lesions accompanied by pruritus and alopecia. A five-year-old female Labrador was brought with erythematous lesions around nose, periorbital area, ears, foot pads and vulva for three days prior to presentation. Cytology revealed acantholytic cells, indicating that the problem was pemphigus. For six weeks, oral immunosuppressive azathioprine and other supportive medications like ranitidine, fexofinadine and niacinamide were recommended. The animal experienced total recovery following treatment.